Characteristics of Falls Among Institutionalized Elderly People - Ahmad Ali Akbari Kamrani; Farhad Azadi; Mahshid Foroughan; Saeid Siadat; Ali Reza Kaldi (University of Social Welfare & Rehabilitation Sciences, 2007)
Objectives: Falls by elderly people area frequent cause of morbidity and mortality, especially in institutionalized elders. to describe the features of falls among institutionalized elderly people. Methods & Materials: characteristics of falls in the preceding six months (March 2006 - September 2006) that occurred among elder lies (aged over 60years) with normal physical function and cognitive status, who lived at Kahrizak Institute, along term nursing home in Tehran, were surveyed and analyzed. Results: The mean age of the patients with falls was 76.9 yrs. These numbers of falls had occurred among 29 elders that 48.3% were women and 51.7% were men. 57.6% off alls were simple and elders could standup immediately independently. 42.4% of falls needed to help for standup, 2 elder person (2.6%) had sever consequence of fall and had fractures. (Skull fracture, head trauma & hip fracture) 30.3% of falls occurred in yard, 28.9% at room, 18.4%inhallway, 14.5% at WC, .3.9%at bathroom, and 3.9% at lunch saloon. Analysis of the time of falls showed: 45.3% of falls occurred at 7bl2 am, 13.2% at the lunch time (12bI4), 17% at 14b19, 11.3%at night (19b4 am), and 13.2% at 4b7 am. Conclusion: falls among elder lies occur mainly outside of room. And occur at the time of maximum activities, for example at morning; also falls have been happened more in subjects older, and occasionally result in sever injury such as head trauma, skull fracture, femur and pelvis fracture and cause more mortality and morbidity. Control of environmental risk factors could be protective factors against falls.